The role of biological nitrogen fixation in polyhydroxybutyrate production from methane by methane-oxidizing bacteria: a review of metabolic routes and yield enhancement - Xie, Jin Hui; Xin, Jia Ying; Sun, Li Rui; Cui, Tian Yu; Bi, Hai Xin; Wang, Yan; Zhang, Jian Xiong (Frontiers in Microbiology, 2025)
In recent years, the synthesis of Polyhydroxybutyrate (PHB) using methane-oxidizing bacteria (MOB) to convert one carbon and N2 resources has received much attention. In addition, nitrogen fixation by nitrogen gas (N2) has an effect on the metabolic pathways of MOB. Although progress has been made in the basic metabolic pathways and the role of key enzymes, there are still many challenges, such as explorating the synergistic mechanism of one carbon and nitrogen and how to optimize the cultivation conditions to increase yield and reduce costs. This paper is concerned with the biological characteristics of methanogens and their role in the metabolism of one carbon and N2 resources. In addition, it introduces the optimization of their PHB synthesis capacity by new technologies in the field of metabolic engineering. The aim of the paper is to provide a theoretical basis for solving plastic pollution and realizing renewable utilization of resources.